The Developmemt of Teaching Materials on The Area of Triangles and Quadrilaterals by Using Geogebra-Assisted Discovery Learning Method to Improve Mathematics Understanding Ability - Niva Ramadhani Putri; Jozua Sabandar; Asep Ikin Sugandi ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2021)
The understanding mathematics ability is a basic ability that is very important and must be possessed by students in learning mathematics. In fact, the ability to understand mathematics is still relatively low, especially in triangles and quadrilaterals. The purpose of this study is to produce teaching materials on triangles and quadrilaterals based on the GeoGebra-assisted discovery learning method that is valid, practical, and effective to improve students' mathematical understanding abilities. The method in this study is the ADDIE type of research & development method. The teaching materials developed in this study were student worksheets and learning videos. The subjects in this study were seventh grade junior high school students. Data processing techniques consist of analysis of the results of the validation of material experts and ICT experts, practicality analysis obtained from the results of filling out questionnaires for student responses to teaching materials, and effectiveness analysis obtained from the results of students' mathematical understanding ability tests. The results of this study are student worksheets and learning videos developed that meet the criteria of being very valid, very practical, and very effective for improving mathematical understanding skills. The developed teaching materials can be used by teachers so that students are able to easily understand the concepts in the area of triangles and quadrilaterals.